Historical biogeography of Boraginales: West Gondwanan vicariance followed by long‐distance dispersal?. (8th August 2016) - Luebert, Federico; Couvreur, Thomas L. P.; Gottschling, Marc; Hilger, Hartmut H.; Miller, James S.; Weigend, Maximilian
Abstract: Aim: To examine the historical biogeography of the Boraginales using molecular dating and ancestral area reconstruction. Location: World‐wide. Methods: We constructed data sets that included all major clades of Boraginales and all orders of asterids using previously published sequences of four plastid markers ( trn L ‐trn F, rps 16, ndh F, rbc L). We estimated divergence times using a Bayesian uncorrelated, lognormal relaxed clock approach with four different fossil calibration schemes. Ancestral areas were reconstructed using maximum likelihood methods (Dispersal‐Extinction‐Cladogenesis). Results: Boraginales originated during the Early to Late Cretaceous and started its diversification in the Late Cretaceous. The inferred ancestral area of Boraginales includes the Americas and Africa. The two major clades of Boraginales diversified during the Early Paleogene from African and American ancestors respectively. Early branching families in both clades (Codonaceae and Wellstediaceae in one clade and Hydrophyllacee and Namaceae in the other) may have remained restricted to their areas of origin. The other families started diversifying in several regions of the world during the Eocene (Boraginaceae s.str., Heliotropiaceae, Ehretiaceae) or later (Cordiaceae). Main conclusions: Molecular dating and ancestral area reconstruction may be broadly consistent with the idea of a vicariant origin of the two major clades of Boraginales after the break‐up of West Gondwana, followed by several independent trans‐oceanic dispersal events into most areas of the world. However, uncertainty in both divergence times and ancestral area reconstruction do not rule out the possibility of an origin involving long‐distance dispersal.